Preparation method of alumina-based composite diaphragm
Functional alumina is prepared by polyethylene glycol grafting method, and combined with film-forming polymers and hydrophilic particles, the problems of poor hydrophilicity and high cost of composite separators are solved, and alumina-based composite separators with low impedance, high hydrophilicity and high stability are achieved.
Patent Information
- Application Number
- CN202411701318.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
AI Technical Summary
When the existing composite separators improve hydrophilic properties, the agglomeration and adhesion of zirconia are reduced, resulting in cracking of the membrane and powder loss, and are costly.
Functional alumina was prepared by polyethylene glycol grafting method, and hydrophilic composite separators were prepared by phase separation method, combining film-forming polymers and hydrophilic particles to enhance the hydrophilicity and stability of the film.
The low cost, high hydrophilicity and high stability of the alumina-based composite separator are achieved, the membrane impedance is reduced, and the application prospects in the production of hydrogen by alkaline electrolysis is improved.
Smart Images

Figure CN119571390A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production composite diaphragm preparation, and in particular relates to a method for preparing an alumina-based composite diaphragm. Background Art
[0002] Hydrogen is the ideal energy source of the 21st century. As a renewable secondary energy source, hydrogen is abundant in source, has high mass energy density and calorific value of up to 143MJ / kg. Hydrogen has the advantages of zero carbon emission and environmental friendliness. In the future, the global demand for hydrogen will increase dramatically, and the development of efficient and low-cost hydrogen production technology will become increasingly important. Hydrogen production by water electrolysis is a zero-emission, reliable industrial application technology, especially when combined with renewable energy sources such as wind and solar energy. However, hydrogen production by alkaline water electrolysis faces the problem of high hydrogen production cost, so it is urgent to significantly reduce the cost of hydrogen production by water electrolysis.
[0003] At present, alkaline electrolyzers are mainly composed of electrodes, catalysts and membranes. There are many ways to reduce the cost of producing hydrogen, such as reducing material costs, increasing operating pressure and temperature, developing efficient catalysts, designing zero-gap membrane electrodes, and exploring high-performance membranes. Among these methods, developing high-performance, low-cost membranes is considered to be one of the most effective strategies. The diaphragm is required not only to separate the generated gas from the cathode and anode, but also to provide an electrolyte transmission channel. Asbestos diaphragm, as the first generation of diaphragm, has good gas barrier properties, but asbestos is eliminated due to its easy decomposition, electrolyte pollution, high resistance, high energy consumption, and its carcinogenicity. Polyphenylene sulfide (PPS) non-woven fabric diaphragm was developed as the second generation of diaphragm, which has the advantages of high temperature resistance and stability to concentrated alkali, but its disadvantages are also obvious, and the energy consumption is relatively high. Therefore, the emergence of the third generation of composite diaphragms marks the entry of diaphragm technology into a new era. This diaphragm has low resistance, low energy consumption, excellent gas barrier properties, high temperature resistance, and good stability to concentrated alkali, so it occupies a dominant position in the market.
[0004] The traditional composite diaphragm is to add hydrophilic inorganic nanoparticles to the PPS diaphragm to increase the hydrophilicity of the diaphragm. Most of the hydrophilic nanoparticles used in the market are zirconium oxide. In order to increase the hydrophilicity of the diaphragm, it is usually necessary to increase the proportion of zirconium oxide added. However, an excessively high proportion of zirconium oxide causes zirconium oxide to agglomerate, and the adhesion between zirconium oxide and the film-forming polymer is weakened, resulting in cracking and powdering of the finished film. In severe cases, the composite diaphragm may rupture, resulting in abnormal shutdown or even explosion due to excessive oxygen in hydrogen. At the same time, the high price of zirconium oxide leads to high manufacturing costs of the finished membrane and low economic efficiency.
[0005] To address the above problems, composite membranes with low construction cost, good hydrophilicity and high stability are currently one of the most promising solutions. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing an alumina-based composite diaphragm.
[0007] The present invention adopts the following technical solution:
[0008] A method for preparing an alumina-based composite diaphragm comprises the following steps:
[0009] Step 1, preparation of polyethylene glycol functionalized alumina
[0010] (1) grinding 25-50 parts by weight of aluminum oxide particles, adding them to 50-75 parts by weight of an ethanol solution for dispersion;
[0011] (2) adding 30-45 parts by weight of polyethylene glycol modifier to 30-45 parts by weight of ethanol solution, 10-20 parts by weight of deionized water, and 0.1-2 parts by weight of hydrochloric acid, stirring and hydrolyzing;
[0012] (3) adding the polyethylene glycol modifier solution hydrolyzed in step (2) to the alumina solution obtained in step (1), and stirring in a constant temperature water bath to allow for a full reaction;
[0013] (4) centrifuging the solution after the reaction, taking out the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina;
[0014] Step 2, weighing 5-10 parts by weight of a film-forming polymer and 40-65 parts by weight of N-methylpyrrolidone into a flask, stirring in a constant temperature water bath, and then adding 10-50 parts by weight of functionalized alumina particles and 5-10 parts by weight of hydrophilic particles, blending and stirring until completely dissolved, and then ultrasonicating at room temperature to mix evenly to form a casting solution;
[0015] Step 3, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping different thicknesses from top to bottom on the glass plate with a scraping knife to obtain single-sided homogeneous films of different specifications;
[0016] Step 4, immersing the PPS base web in the single-sided homogeneous film, and after pre-evaporation in the air, repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film;
[0017] Step 5, placing the double-sided coated film obtained in step (4) into deionized water to solidify into a film, washing away the residual solvent, falling off from the glass plate after soaking, taking it out from the coagulation bath, washing with deionized water, and drying to obtain a composite diaphragm.
[0018] Furthermore, the molecular weight of the polyethylene glycol modifier is in the range of 400-6000.
[0019] Furthermore, the polyethylene glycol modifier is one or more of polyethylene glycol trimethoxysilyl propyl ether, methoxy polyethylene glycol silane, maleimide polyethylene glycol silane, triethoxysilane polyethylene glycol hydroxyl.
[0020] Furthermore, the film-forming polymer is one or more of polyetherketoneketone, polyimide, sulfonated polyethersulfone, and sulfonated polysulfone.
[0021] Furthermore, the hydrophilic particles are one or more of yttrium oxide, barium oxide, titanium oxide, silicon oxide, and calcium oxide.
[0022] Furthermore, the particle size of the alumina particles after grinding is in the range of 20-800 nm, and the concentration of the ethanol solution is in the range of 75-99%.
[0023] Furthermore, in step 1, the grinding time is 10-60 min, the stirring and hydrolysis time is 2-8 h; the constant temperature water bath temperature is 30-70° C., the water bath stirring time is 6-12 h; and the centrifugal speed is 6000-10000 rpm / min.
[0024] Furthermore, in step 2, the constant temperature water bath temperature of the film-forming polymer and N-methylpyrrolidone is 30-70°C, the stirring time is 2-6 hours, the functionalized alumina particles and the hydrophilic particles are added and mixed and stirred for 8-12 hours; the casting liquid is ultrasonicated at room temperature for 30-180 minutes.
[0025] Furthermore, in step 3, the coating thickness of the scraper is 100-500 μm; in step 4, the pre-evaporation time is 30-600 s; in step 5, the coagulation bath temperature is 5-85° C., and the immersion time is 10-100 min.
[0026] Furthermore, the thickness of the alumina-based composite diaphragm is 400-500 μm.
[0027] It can be seen from the above description of the present invention that, compared with the prior art, the present invention has the following beneficial effects:
[0028] First, the present invention adopts polyethylene glycol grafting method to prepare hydrophilic alumina, and adopts phase separation method to prepare hydrophilic composite diaphragm. This composite diaphragm has the advantages of good hydrophilicity, low impedance, good stability, good alkali resistance and chemical corrosion resistance. Among them, alumina is a common ceramic material, which is widely used in the preparation of membranes due to its low manufacturing cost, easy availability, resistance to organic solvents and other characteristics. However, the hydrophilicity of alumina itself is poor, resulting in large impedance and poor electrolytic performance of the prepared diaphragm. Alumina needs to be modified to solve the problem of poor hydrophilicity; therefore, polyethylene glycol modifier is selected to graft alumina to prepare functionalized alumina particles to form stable chemical bonds; the modified alumina particles are composited with film-forming polymers, retaining the advantages of functionalized alumina particles, and adding hydrophilic particles to synergistically enhance hydrophilicity, further reduce impedance, and increase the application prospects of composite diaphragms in alkaline water electrolysis to produce hydrogen;
[0029] Second, the technical solution of the present invention solves the problems of high cost and poor hydrophilicity of the composite diaphragm, effectively reduces the cost, enhances the hydrophilicity of the alumina-based composite diaphragm, and reduces the diaphragm impedance;
[0030] Thirdly, the preparation method of the alumina-based composite membrane provided by the present invention is simple and easy to operate, and can be used in commercial application production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the preparation process of the composite diaphragm proposed in the examples and comparative examples of the present application;
[0032] Figure 2 Electron microscope photographs of the composite diaphragms proposed in Example 4 and Comparative Examples 1-3 of the present application;
[0033] Figure 3 This is a graph showing the relationship between voltage and current density of the composite diaphragm proposed in the examples and comparative examples of the present application in a 30 wt % KOH solution at 80°C;
[0034] Figure 4 The composite diaphragm proposed in Example 4 of the present application is at 2.0A / cm 2 , 80℃, electrolytic stability test diagram in 30wt% KOH solution;
[0035] Figure 5 This is a graph showing the mass loss of the composite membranes proposed in Example 4 of the present application and Comparative Examples 1-3 in a 30 wt % KOH solution at 80°C. DETAILED DESCRIPTION
[0036] The present invention is further described below through specific implementation modes.
[0037] A method for preparing an alumina-based composite diaphragm comprises the following steps:
[0038] Step 1, preparation of polyethylene glycol functionalized alumina
[0039] (1) grinding 25-50 parts by weight of aluminum oxide particles for 10-60 minutes to a particle size of 20-800 nm, and then adding the particles to 50-75 parts by weight of an ethanol solution having a concentration range of 75-99% and dispersing the solution;
[0040] (2) adding 30-45 parts by weight of polyethylene glycol modifier to 30-45 parts by weight of ethanol solution, 10-20 parts by weight of deionized water, and 0.1-2 parts by weight of hydrochloric acid, stirring and hydrolyzing for 2-8 hours;
[0041] (3) adding the polyethylene glycol modifier solution hydrolyzed in step (2) to the alumina solution obtained in step (1), stirring in a constant temperature water bath at a temperature of 30-70° C. for 6-12 hours to allow the reaction to proceed fully;
[0042] (4) centrifuging the reaction solution at a speed of 6000-10000 rpm / min, taking the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina;
[0043] Step 2, weighing 5-10 parts by weight of a film-forming polymer and 40-65 parts by weight of N-methylpyrrolidone into a flask, stirring in a constant temperature water bath at a temperature of 30-70°C for 2-6 hours, then adding 10-50 parts by weight of functionalized alumina particles and 5-10 parts by weight of hydrophilic particles, mixing and stirring for 8-12 hours until completely dissolved, and then ultrasonicating at room temperature for 30-180 minutes, mixing evenly to form a casting solution;
[0044] Step 3, pour the casting solution onto a glass plate at room temperature, and then use a scraper to quickly scrape the glass plate from top to bottom with a thickness of 100-500 μm to obtain single-sided homogeneous films of different specifications;
[0045] Step 4, immersing the PPS base web in the single-sided homogeneous film, pre-evaporating in air for 30-600 seconds, and then repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film;
[0046] Step 5, placing the double-sided coated film obtained in step (4) into deionized water at 5-85°C to solidify into a film, washing away the residual solvent, soaking for 10-100 minutes and then falling off the glass plate, taking it out from the coagulation bath, washing with deionized water and drying to obtain a composite diaphragm with a thickness of 400-500μm.
[0047] Among them, the molecular weight range of the polyethylene glycol modifier is 400-6000; the film-forming polymer is one or more of polyetherketoneketone, polyimide, sulfonated polyethersulfone, and sulfonated polysulfone; the hydrophilic particles are one or more of yttrium oxide, barium oxide, titanium oxide, silicon oxide, and calcium oxide; specifically, the polyethylene glycol modifier is one or more of polyethylene glycol trimethoxysilyl propyl ether, methoxy polyethylene glycol silane, maleimide polyethylene glycol silane, and triethoxysilane polyethylene glycol hydroxyl.
[0048] Example 1
[0049] A method for preparing an alumina-based composite diaphragm comprises the following steps:
[0050] Step 1, preparation of polyethylene glycol functionalized alumina
[0051] (1) Grind 50.0 g of alumina particles for 10 min, take them out and disperse them in 100.0 g of ethanol;
[0052] (2) Add 2.5 g of polyethylene glycol trimethoxysilyl propyl ether to 2.5 g of ethanol, 1.0 g of deionized water, and 0.05 g of 1 mol / L hydrochloric acid, and stir to hydrolyze for 2 h;
[0053] (3) adding the hydrolyzed polyethylene glycol modifier solution to the alumina solution and stirring in a constant temperature water bath at 30° C. for 6 h to allow for a full reaction;
[0054] (4) centrifuging the reaction solution at 6000 rpm, taking the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina;
[0055] Step 2, weigh 11.2 g of polyimide into a flask, add 96 g of N-methylpyrrolidone, stir for 2 h in a constant temperature water bath at 50° C., then add 42.0 g of functionalized alumina particles and 12.0 g of silicon oxide, mix and stir for 8 h until completely dissolved, then perform ultrasound at room temperature for 30 min, mix evenly, and form a casting solution;
[0056] Step 3, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0057] Step 4, immersing the PPS base mesh in the single-sided homogeneous film, pre-evaporating in air for 30 seconds, and then repeating the above-mentioned film scraping operation on the PPS base mesh to obtain a double-sided coating film;
[0058] Step 5, put it into deionized water at 5°C to solidify into a film, wash away the residual solvent, soak it for 30 minutes, fall off from the glass plate, take it out from the solidification bath, wash it with deionized water, and dry it to obtain a composite diaphragm.
[0059] Example 2
[0060] A method for preparing an alumina-based composite diaphragm comprises the following steps:
[0061] Step 1, preparation of polyethylene glycol functionalized alumina
[0062] (1) Grind 50.0 g of alumina particles for 10 min, take them out and disperse them in 100.0 g of ethanol;
[0063] (2) Add 5.0 g of polyethylene glycol trimethoxysilyl propyl ether to 5.0 g of ethanol, 1.5 g of deionized water, and 0.10 g of 1 mol / L hydrochloric acid, and stir and hydrolyze for 2 h, and then stir and hydrolyze for 3 h;
[0064] (3) adding the hydrolyzed polyethylene glycol modifier solution to the alumina solution and stirring in a constant temperature water bath at 40° C. for 7 h to allow for a full reaction;
[0065] (4) centrifuging the reaction solution at 7000 rpm, taking the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina;
[0066] Step 2, weigh 11.2 g of polyetherketoneketone into a flask, add 96 g of N-methylpyrrolidone, stir for 3 h in a constant temperature water bath at 50 ° C, then add 44.0 g of functionalized alumina particles and 10.0 g of titanium oxide, mix and stir for 9 h until completely dissolved, then ultrasonicate at room temperature for 50 min, mix evenly, and form a casting solution;
[0067] Step 3, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0068] Step 4, immersing the PPS base mesh in the single-sided homogeneous film, pre-evaporating in air for 60 seconds, and repeating the above-mentioned film scraping operation on the PPS base mesh to obtain a double-sided coating film;
[0069] Step 5, put it into deionized water at 15°C to solidify into a film, wash away the residual solvent, soak for 45 minutes, fall off from the glass plate, take it out from the solidification bath, wash with deionized water, and dry to obtain a composite diaphragm.
[0070] Example 3
[0071] A method for preparing an alumina-based composite diaphragm comprises the following steps:
[0072] Step 1, preparation of polyethylene glycol functionalized alumina
[0073] (1) Grind 50.0 g of alumina particles for 10 min, take them out and disperse them in 100.0 g of ethanol;
[0074] (2) Add 7.5 g of polyethylene glycol trimethoxysilyl propyl ether to 7.5 g of ethanol, 2.0 g of deionized water, and 0.15 g of 1 mol / L hydrochloric acid, and stir to hydrolyze for 4 h;
[0075] (3) adding the hydrolyzed polyethylene glycol modifier solution to the alumina solution and stirring in a constant temperature water bath at 50° C. for 8 h to allow for sufficient reaction;
[0076] (4) centrifuging the reaction solution at 8000 rpm, taking the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina;
[0077] Step 2, weigh 11.2 g of sulfonated polyethersulfone into a flask, add 96 g of N-methylpyrrolidone, stir for 4 h in a constant temperature water bath at 50 ° C, then add 46.0 g of functionalized alumina particles and 8.0 g of calcium oxide, mix and stir for 10 h until completely dissolved, then ultrasonicate at room temperature for 70 min, mix evenly, and form a casting solution;
[0078] Step 3, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0079] Step 4, immersing the PPS base web in the single-sided homogeneous film, pre-evaporating in air for 90 seconds, and then repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film;
[0080] Step 5, put it into deionized water at 25°C to solidify into a film, wash away the residual solvent, soak for 60 minutes, fall off from the glass plate, take it out from the solidification bath, wash with deionized water, and dry to obtain a composite diaphragm.
[0081] Example 4
[0082] A method for preparing an alumina-based composite diaphragm comprises the following steps:
[0083] Step 1, preparation of polyethylene glycol functionalized alumina
[0084] (1) Grind 50.0 g of alumina particles for 10 min, take them out and disperse them in 100.0 g of ethanol;
[0085] (2) Add 10.0 g of polyethylene glycol trimethoxysilyl propyl ether to 10.0 g of ethanol, 2.5 g of deionized water, and 0.20 g of 1 mol / L hydrochloric acid, and stir to hydrolyze for 5 h;
[0086] (3) adding the hydrolyzed polyethylene glycol modifier solution to the alumina solution and stirring in a constant temperature water bath at 60° C. for 9 h to allow for a full reaction;
[0087] (4) centrifuging the reaction solution at 9000 rpm, taking the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina;
[0088] Step 2, weigh 11.2 g of sulfonated polysulfone into a flask, add 96 g of N-methylpyrrolidone, stir for 5 h in a constant temperature water bath at 50 ° C, then add 48.0 g of functionalized alumina particles and 6.0 g of yttrium oxide, mix and stir for 11 h until completely dissolved, then ultrasonicate at room temperature for 80 min, mix evenly, and form a casting solution;
[0089] Step 3, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0090] Step 4, immersing the PPS base mesh in the single-sided homogeneous film, pre-evaporating in air for 120 seconds, and repeating the above-mentioned film scraping operation on the PPS base mesh to obtain a double-sided coating film;
[0091] Step 5, put it into deionized water at 35°C to solidify into a film, wash away the residual solvent, soak for 75 minutes, fall off from the glass plate, take it out from the solidification bath, wash with deionized water, and dry to obtain a composite diaphragm.
[0092] Comparative Example 1
[0093] A method for preparing a composite diaphragm comprises the following steps:
[0094] Step 1, weigh 11.2 g of sulfonated polysulfone into a flask, add to 96 g of N-methylpyrrolidone, stir for 5 h in a constant temperature water bath at 50° C., then add 54.0 g of zirconium oxide particles, mix and stir for 11 h until completely dissolved, then ultrasonicate at room temperature for 80 min, mix evenly, and form a casting solution;
[0095] Step 2, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0096] Step 3, immersing the PPS base web in the single-sided homogeneous film, pre-evaporating in air for 120 seconds, and then repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film;
[0097] Step 4, put it into deionized water at 35°C to solidify into a film, wash away the residual solvent, soak for 75 minutes, fall off from the glass plate, take it out from the solidification bath, wash with deionized water, and dry to obtain a composite diaphragm.
[0098] Comparative Example 2
[0099] A method for preparing a composite diaphragm comprises the following steps:
[0100] Step 1, weigh 11.2 g of sulfonated polysulfone into a flask, add to 96 g of N-methylpyrrolidone, stir for 5 h in a constant temperature water bath at 50° C., then add 54.0 g of alumina particles, mix and stir for 11 h until completely dissolved, then ultrasonicate at room temperature for 80 min, mix evenly, and form a casting solution;
[0101] Step 2, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0102] Step 3, immersing the PPS base web in the single-sided homogeneous film, pre-evaporating in air for 120 seconds, and then repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film;
[0103] Step 4, put it into deionized water at 35°C to solidify into a film, wash away the residual solvent, soak for 75 minutes, fall off from the glass plate, take it out from the solidification bath, wash with deionized water, and dry to obtain a composite diaphragm.
[0104] Comparative Example 3
[0105] A method for preparing a composite diaphragm comprises the following steps:
[0106] Step 1, weigh 11.2g of sulfonated polysulfone into a flask, add 96g of N-methylpyrrolidone, stir for 5h in a constant temperature water bath at 50°C, then add 48.0g of alumina particles and 6.0g of yttrium oxide, stir for 11h until completely dissolved, then perform ultrasound at room temperature for 80min, mix evenly, and form a casting solution. After stirring, remove the casting solution;
[0107] Step 2, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping the glass plate from top to bottom with a scraping knife to a thickness of 300 μm to obtain single-sided homogeneous films of different specifications;
[0108] Step 3, immersing the PPS base web in the single-sided homogeneous film, pre-evaporating in air for 120 seconds, and then repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film;
[0109] Step 4, put it into deionized water at 35°C to solidify into a film, wash away the residual solvent, soak for 75 minutes, fall off from the glass plate, take it out from the solidification bath, wash with deionized water, and dry to obtain a composite diaphragm.
[0110] The alumina-based composite membranes prepared in Examples 1-4 and the composite membranes prepared in Comparative Examples 1-3 were tested accordingly. The specific structures are shown in Table 1. Figure 1-4 .
[0111] Table 1 Performance test results of composite diaphragms prepared in the examples of the present application and the comparative examples
[0112]
[0113] Referring to Table 1, it can be seen that the composite membranes of Examples 1-4 have smaller alkali liquid contact angles on the membrane surface and stronger hydrophilicity than the composite membranes of Comparative Examples 1-3, and as the amount of functionalized alumina particles added increases, the hydrophilicity of the membrane also decreases, wherein the minimum value of Example 4 can reach 55°, which is based on the excellent hydrophilicity of the hydrophilic modified alumina particles; the alkaline water electrolysis hydrogen production membranes of Examples 1-4 have smaller membrane impedance than the composite membranes of Comparative Examples 1-3, and as the amount of functionalized alumina particles added increases, the membrane impedance also decreases, wherein the minimum value of Example 4 can reach 0.17Ω / cm 2 The low impedance of the composite membrane ensures the high current density performance of the composite membrane; the composite membranes of Examples 1-4 have a larger bubble point than the composite membranes of Comparative Examples 1-3, wherein the maximum bubble point of Example 4 can reach 4.4 bar, which is attributed to the fact that the polyethylene glycol functional alumina improves the overall dispersion, reduces agglomeration, and the membrane surface tends to be dense, thereby improving the hydrophilicity of the membrane while ensuring the gas barrier property of the membrane.
[0114] according to Figure 2 It can be seen that after 1200 hours of electrolytic performance testing, the inorganic particles are still adhered to the surface / interior of the composite diaphragms of Example 4 (a), Comparative Example 2 (c) and Comparative Example 3 (d), and no obvious shedding occurs; however, after 1200 hours of electrolytic performance testing, inorganic particles partially fall off on the surface of the composite diaphragm of Comparative Example 1 (b), leaving large pores on the surface.
[0115] according to Figure 3 It can be seen that compared with the composite membranes of Comparative Examples 1-3, the composite membranes of Examples 1-4 have an increased current density at 2.0 V as the amount of functionalized alumina particles added increases, and Example 4 has the best performance, reaching 2.5 A / cm 2 , ensuring high electrolysis efficiency.
[0116] according to Figure 4-5 It can be seen that under the test of 80°C and 30wt% KOH solution, the electrolysis performance of the alumina-based composite diaphragm of Example 4 is basically stable over a long period of time; compared with the zirconium oxide-based composite diaphragm of Comparative Example 2, the alumina-based composite diaphragms of Example 4, Comparative Example 2 and Comparative Example 3 have less mass loss under long-term testing, thereby ensuring the stability and durability of the composite diaphragm.
[0117] The technical solution of the present invention solves the problems of high cost and poor hydrophilicity of composite diaphragms, effectively reduces costs, enhances the hydrophilicity of alumina-based composite diaphragms, and reduces diaphragm impedance; and the preparation method is simple and easy to operate, which increases the application prospect of composite diaphragms in alkaline water electrolysis to produce hydrogen, and can be used in commercial application production.
[0118] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. That is, equivalent changes and modifications made according to the application scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing an alumina-based composite diaphragm, characterized in that: The following steps are involved: Step 1, preparation of polyethylene glycol functionalized alumina (1) grinding 25-50 parts by weight of aluminum oxide particles, adding them to 50-75 parts by weight of an ethanol solution for dispersion; (2) adding 30-45 parts by weight of polyethylene glycol modifier to 30-45 parts by weight of ethanol solution, 10-20 parts by weight of deionized water, and 0.1-2 parts by weight of hydrochloric acid, stirring and hydrolyzing; (3) adding the polyethylene glycol modifier solution hydrolyzed in step (2) to the alumina solution obtained in step (1), and stirring in a constant temperature water bath to allow for a full reaction; (4) centrifuging the solution after the reaction, taking out the precipitate, washing it with ethanol for multiple times, and drying it to obtain polyethylene glycol functionalized alumina; Step 2, weighing 5-10 parts by weight of a film-forming polymer and 40-65 parts by weight of N-methylpyrrolidone into a flask, stirring in a constant temperature water bath, and then adding 10-50 parts by weight of functionalized alumina particles and 5-10 parts by weight of hydrophilic particles, blending and stirring until completely dissolved, and then ultrasonicating at room temperature to mix evenly to form a casting solution; Step 3, pouring the casting solution onto a glass plate at room temperature, and then quickly scraping different thicknesses from top to bottom on the glass plate with a scraping knife to obtain single-sided homogeneous films of different specifications; Step 4, immersing the PPS base web in the single-sided homogeneous film, and after pre-evaporation in the air, repeating the above-mentioned film scraping operation on the PPS base web to obtain a double-sided coating film; Step 5, placing the double-sided coated film obtained in step (4) into deionized water to solidify into a film, washing away the residual solvent, falling off from the glass plate after soaking, taking it out from the coagulation bath, washing with deionized water, and drying to obtain a composite diaphragm.
2. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: The molecular weight of the polyethylene glycol modifier is in the range of 400-6000.
3. The method for preparing an alumina-based composite diaphragm according to claim 2, characterized in that: The polyethylene glycol modifier is one or more of polyethylene glycol trimethoxysilyl propyl ether, methoxy polyethylene glycol silane, maleimide polyethylene glycol silane, triethoxysilane polyethylene glycol hydroxyl.
4. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: The film-forming polymer is one or more of polyetherketoneketone, polyimide, sulfonated polyethersulfone and sulfonated polysulfone.
5. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: The hydrophilic particles are one or more of yttrium oxide, barium oxide, titanium oxide, silicon oxide, and calcium oxide.
6. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: The particle size of the aluminum oxide particles after grinding is in the range of 20-800 nm, and the concentration of the ethanol solution is in the range of 75-99%.
7. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: In step 1, the grinding time is 10-60 minutes, the stirring and hydrolysis time is 2-8 hours; the constant temperature water bath temperature is 30-70° C., the water bath stirring time is 6-12 hours; and the centrifugal speed is 6000-10000 rpm / min.
8. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: In step 2, the constant temperature water bath temperature of the film-forming polymer and N-methylpyrrolidone is 30-70°C, the stirring time is 2-6 hours, the functionalized alumina particles and hydrophilic particles are added and mixed and stirred for 8-12 hours; the casting solution is ultrasonicated at room temperature for 30-180 minutes.
9. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: In step 3, the coating thickness of the scraper is 100-500 μm; in step 4, the pre-evaporation time is 30-600 s; in step 5, the coagulation bath temperature is 5-85° C., and the immersion time is 10-100 min.
10. The method for preparing an alumina-based composite diaphragm according to claim 1, characterized in that: The thickness of the alumina-based composite diaphragm is 400-500 μm.
Citation Information
Cited By
Alkaline electrolyzed water composite diaphragm based on hydroxyl alumina and preparation method of alkaline electrolyzed water composite diaphragm
CN121556087A